Shadows of the Past: The Effect of Communist Heritage on Employee Consultation. (May 2016) - Oertel, Simon; Thommes, Kirsten; Walgenbach, Peter
Following research on transition economies in Central and Eastern Europe (CEE), and having been motivated by arguments pertaining to the business systems approach, the authors propose that the existence of a communist heritage decreases the likelihood that employees will be consulted during organizational change processes. Results based on 23, 876 firms across 27 of the European Union (EU-27) countries support this proposition. Moreover, the likelihood of direct consultation decreases with the existence of formal employee representation and an increasing share of foreign ownership in firms located in CEE countries. The authors discuss these findings in the context of organizational democracy research and the recent literature on transition economies and contribute to a more comprehensive understanding of participative decision-making processes in organizations.